Association between antepartum depressive symptoms and prenatal care utilization and milestones: a retrospective cohort study - Minyoung Jang; Malini Ramaiyer; Sarah Olson; Kristin Voegtline; Cybill Esguerra (BMC Pregnancy and Childbirth)
Abstract Background To evaluate the relationship between antepartum depressive symptoms and prenatal care utilization and completion of prenatal care milestones, namely, routine screening tests and vaccinations in pregnancy. Methods This retrospective cohort includes pregnant individuals who completed first or second trimester screening using the Edinburgh Postnatal Depression Scale (EPDS) between 2020 and 2021. Baseline characteristics were compared between individuals who screened positive versus negative for depression. Multivariable logistic regression models were used to estimate odds of completing third trimester prenatal care milestones, including sexually transmitted infection screening, glucose tolerance testing, group B streptococcus testing, and tetanus toxoid, reduced diphtheria toxoid, and acellular pertussis (Tdap) vaccination. Results Of 718 individuals who completed the EPDS in early pregnancy, 85 (11.8%) screened positive for depressive symptoms. A greater proportion of these individuals were younger (median age 28 vs. 31 years, P =.034), unpartnered (P =.005), publicly insured (P =.013), had a history of substance use (P <.001) or prior psychiatric diagnosis (P <.001), and entered prenatal care at later gestational ages (median 12.3 vs. 10.7 weeks, P =.002) than those who screened negative. Although there were no significant differences in total prenatal care visits attended between groups (P =.123), the adjusted odds of completing third trimester milestones including glucose tolerance testing (OR [95% CI] 0.60 [0.36–0.98]) and group B streptococcus testing (OR 0.56 [0.33–0.95]) were lower among individuals who screened positive for depressive symptoms. Less than half of individuals at risk for depression who were referred to mental health services successfully completed consultations during pregnancy. Conclusions Pregnant individuals who screen positive for depressive symptoms in early pregnancy comprised a socially vulnerable group at risk of missing third trimester prenatal care milestones. Mental health screening and integrated interventions across the perinatal continuum may help mitigate the current treatment gap for patients in need of mental health services during pregnancy.